Preservation of Affordable Rental Housing Evaluation of the MacArthur Foundation's Window of Opportunity Initiative - Schwartz, Heather L. (RAND Corporation, 2016)
In 2000, the MacArthur Foundation began the Window of Opportunity, a 20-year, $187 million philanthropic initiative intended to help preserve privately owned affordable rental housing. The authors of this report assess whether the initiative achieved its goals and identify lessons learned about effective preservation practices, as well as about the implementation of large-scale philanthropic initiatives generally.